Implementation of Performance-Based Budget on Ternate Resort Police Task Force - Marsudi Marsudi; Abdul Hadi Sirat; Hartaty Hadady (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The purpose of this study is to examine the implementation of performance-based budgets at Satker (Task Force) Polres (Resort Police) Ternate in terms of planning, implementation (including transparent and accountability), evaluation, performance measurement, effectiveness, and efficiency. using qualitative descriptive approaches with 5 informants and documentation study studies The outcomes revealed from the perspective of planning seen the process that has been procedurally seen the relationship between Renstra, Renja, and RKA and budget preparation done bottom up. However, several challenges remain in its implementation, particularly a shortage of HR expertise in linked roles. Aspects of implementation reviewed from transparency show that all members and functional units are aware of the budget allocation of each of these things seen from Kasatker's attention to socializing RKA/DIPA, in terms of accountability seen to comply with budgeting mechanisms and can be accounted for and can be assessed success or failure in the achievement of targets Evaluation is carried out on a regular basis to determine the extent to which budget realization has been achieved and to identify problems connected to budget use. The achievements of each strategic target indication are observed in performance measurement.